Colloidal assembly of polydisperse particle blends during drying. Issue 36 (19th August 2020) - Dong, Yichen; Busatto, Nicolas; Roth, Peter J.; Martin-Fabiani, Ignacio
Abstract : Polydisperse particle blends hold great potential for controlling size segregation during drying when varying evaporation rate. Abstract : In this work, we synthesize a polydisperse aqueous colloidal system composed of small and large zwitterionic particles, as well as medium sized standard acrylic particles. By assembling these dispersions into films by drying, we show using atomic force microscopy (AFM) how their top surfaces can be mostly covered by zwitterionic groups for a wide range of evaporation rates. We probe underneath the top film surface using Fourier-transform infrared (FTIR) spectroscopy – attenuated total reflection (ATR), observing that the content in zwitterionic particles of the film upper layer increases for faster evaporation rates. We show how polydisperse systems hold great potential to overcome the evaporation rate dependence of size segregation processes in drying colloidal blends, and we provide further insights into the assembly mechanisms involved. Polydisperse blends enhance the robustness of such processes for application in coatings and other soft products where evaporation rate can not be tuned.